👤

Answer :

Answer:

Explanation:

The general expression of a quadratic equation is;

[tex]ax^2+bx+c=0[/tex]

Given the quadratic expression

[tex]8x^2+7x=-1[/tex]

Firstly, we need to re-arrange and equate the expression to zero.

[tex]8x^2+7x+1=0[/tex]

To factorize this expression, we will use the general formula:

[tex]x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}[/tex]

From the expression given, we can see that a = 8, b = 7 and c = 1

Substitute these values into the general formula as shown:

[tex]\begin{gathered} x=\frac{-7\pm\sqrt[]{7^2-4(8)(1)}}{2(8)} \\ x=\frac{-7\pm\sqrt[]{49-32}}{16} \\ x=\frac{-7\pm\sqrt[]{17}}{16} \\ x=\frac{-7\pm4.123}{16} \end{gathered}[/tex]

Get the required values of x:

[tex]\begin{gathered} x=\frac{-7+4.123}{16}\text{ and }\frac{-7-4.123}{16} \\ x=\frac{-2.877}{16}\text{and }\frac{-11.123}{16} \\ x\approx-0.18\text{ and -}0.70 \end{gathered}[/tex]

This shows that the solution to the quadratic equation is (-0.18, -0.70)

Go Teaching: Other Questions